ANALISIS PEMASARAN DAN DISTRIBUSI IKAN NILA SEGAR (Oreochromis niloticus) DI PASAR BAUNTUNG BANJARBARU PROVINSI KALIMANTAN SELATAN - Yuliyarabihati Yuliyarabihati; Emmy S Mahreda; Irma Febrianty (EnviroScienteae, 2016)
The purpose of this study was to find out differences in marketing margin of tilapia and the factors that influence it, to know the structure, behavior and appearance of tilapia fish market, to  know the benefits received by tilapia traders in Banjarbaru, and analyze the strategies and policies of the local government towards the system that has been running. The research was started from October 2014 until December 2014. The research location was determined intentionally (purposive), i.e. Bauntung Market Banjarbaru, South Kalimantan. It was intended to know prices and marketing costs at the retailer level. The results showed that the analysis of marketing margins of the value of marketing margin was relatively constant/was not much different. Based on F test of all the factors that influenced the marketing margin, they were  free variable volume of marketing (X1), transportation costs (X4), cost of sales (X5) and profit of traders (X6), with 99% confidence level, it was found that there was no real effect on the marketing margin of tilapia. While the selling price (X2), the purchasing price (X3) at 99% confidence level really influenced the marketing margin of tilapia  in Banjarbaru. The analysis of market integration indicated that I () = 0867, which means that market integration was not perfectly integrated yet. This means that the marketing of tilapia in Bauntung Market Banjarbaru was in imperfect competitive market structure. The value of relationship of price changes amounted to 0.87 (r ≠ 1). This means that the relationship of price changes in traders level and the price change in retailers level were not strong (not perfect). The elasticity value of price transmission (ET) was low. The transmission elasticity was <1, the value was 0.763. This means that the price elasticity inelastic or in other words the market is not efficient. The benefits gained by retailers was in average Rp. 2.213,88-/kg.